Residents’ Negative Perception of Fellow Countryman’s Travelling During Epidemiological Restrictions - Chevtaeva, Natalia; Chevtaeva, Ekaterina; Gamor, Emmanuel (Journal of Sociology: Bulletin of Yerevan University, 2023)
This research explored the creation of negative perception towards returning travellers in response to the threat of spreading the virus and positive travel behaviour during the relaxation of travel restrictions at the time of the COVID-19 health crisis. The data for research was collected from 530 respondents and analysed using hierarchical multiple regression, confirmatory factor analysis, and the Sobel test of significance. The study results revealed that people had a perception of a high risk of catching COVID-19, which has led to a negative perception of travel during a pandemic. Moreover, malicious travel behaviour reinforced discrimination, while positive travel behaviour reduced the negativity in perceptions of returning travellers but did not spare the returnees from discrimination. Implications for both practice and theory, as well as limitations and future directions are further discussed. Based on research findings, resilience of travel should not limit its focus on just the recovery and health control measures of regions that receive travellers, but also pay close attention to the perceptions of travellers returning home after vacations, so as to avoid social distress and stimulate a continuous growth of the demand for travel. In order to stimulate sustainable travel activity with no negative perception of travel and travellers among resident, maintaining local getaways is recommended.
Keywords: hierarchical multiple regression; risk management; travel behaviour; COVID-19; recovery marketing